Mobile Application Integration for Grammar Learning: A Quasi-Experimental Study in Indonesian Context - Ahmad, Darmi; Ridwan, Ridwan; Isma, Adi; Amrang, Amrang; Rusdiah, Rusdiah (Universitas Sulawesi Barat, 2025)
Mastering grammatical structures remains challenging for English as a Foreign Language learners in contexts with limited authentic language exposure. This quasi-experimental study examined whether mobile application integration could enhance Simple Present Tense acquisition among 34 seventh-grade students at a public junior high school in Majene, Indonesia. Participants were assigned to either an experimental group (n=17) receiving instruction through the English Grammar: Learn and Test application or a control group (n=17) following conventional textbook-based methods. Pre-test and post-test assessments measured grammar mastery across parts of speech, inflection, and syntax dimensions. Results revealed substantial improvement in the experimental group, with mean scores increasing from 20.94 to 72.12 (p < .001, Cohen's d = 1.95), while the control group showed modest gains (29.18 to 50.94). Notably, 82.4% of experimental participants achieved mastery level compared to 11.8% in the control group. Student perceptions measured through a 15-item questionnaire indicated strong acceptance (M = 4.31), with particularly high ratings for perceived usefulness. Despite sample size limitations, findings suggest that strategically integrated mobile applications can significantly enhance grammar learning when traditional methods prove insufficient, offering practical solutions for resource-constrained educational settings.